2007
DOI: 10.1097/jgp.0b013e3180325a16
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical Characteristics of Geriatric Apathy and Depression: A Magnetic Resonance Imaging Study

Abstract: Apathy and depression were associated with different anatomical correlates in the prefrontal regions implicated in the regulation of cognition and emotion. Our findings offer new understanding of the neuroanatomical characteristics of apathy and depression in late life, and have broad implications for the neurobiology of behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
3
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(110 citation statements)
references
References 62 publications
1
103
3
3
Order By: Relevance
“…Our study has several strengths, including a relatively large group of participants compared with other structural MRI analyses in late life depression, which typically have samples of 20-50 participants (Ballmaier et al, 2004;Lavretsky et al, 2007). This allowed us to control for agerelated structural changes of the gray matter.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several strengths, including a relatively large group of participants compared with other structural MRI analyses in late life depression, which typically have samples of 20-50 participants (Ballmaier et al, 2004;Lavretsky et al, 2007). This allowed us to control for agerelated structural changes of the gray matter.…”
Section: Discussionmentioning
confidence: 99%
“…Despite positive findings in other limbic regions in patients with MDD (eg, hippocampus; (Sheline et al, 1999)), the relation between treatment with antidepressants and ACC volume has not been systematically examined. While it is notable that in several studies reporting small ACC volumes, patients with MDD were free of medication for periods ranging between 2 and 4 weeks (Drevets et al, 1997;Lavretsky et al, 2007;Caetano et al, 2006;Ballmaier et al, 2004); it is unknown whether the withdrawal of antidepressants influenced the pattern of findings reported. Medication history is an important factor in studies of patients with MDD (Dickstein et al, 2005;Strasser et al, 2005;Frazier et al, 2005;Rajkowska, 2002) and our data further support the notion that even relatively short-term treatment may exert a measurable effect on the volumes of key brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Bremner et al (2002) and Pizzagalli et al (2004), who found no differences in BA25 or in BA32 (Bremner et al, 2002) volume between MDD patients and healthy controls, Coryell et al (2005) subsequently reported a reduction in left subcallosal gyrus volume in patients with MDD relative to controls. Finally, a number of studies demonstrate smaller gray (Lavretsky et al, 2007;Caetano et al, 2006;Ballmaier et al, 2004) and white (Ballmaier et al, 2004) matter volume in 'total' and in ventral (Tang et al, 2007) ACC in patients with MDD relative to controls; however, the cingulate regions assayed in these studies varied widely. A small number of studies have relied upon voxel-based morphometry (Pizzagalli et al, 2004;Chen et al, 2007;Tang et al, 2007) as opposed to manual delineation, as is common across the majority of studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, existing studies suggest that the frontal and striatal areas are most robustly implicated in PD patients with symptoms of depression, anxiety or apathy. The frontostriatal pathway has been demonstrated to be the significant neural system affected by geriatric depression, anxiety and apathy 70, 71, 72. Arguably this pathway (Fig.…”
Section: Methodsmentioning
confidence: 99%